Delhi's Marginalized Women Excluded from Training on Adapting to Climate Change. Issue 1 (June 2018) - Saini, Sakshi
Various policies and programmes have been launched in India to enhance the adaptive capacities of vulnerable groups to climate change. However, an assessment of the adaptive abilities of urban poor women living in the National Capital Region of Delhi, India, to climate change shows that marginalized groups have been excluded from access to required information. It recommends the urgent need to provide knowledge on how to adapt to the effects of climate change to the most vulnerable sections of society.